Derivation and Inflection in Taylor Swift’s The Life of a Showgirl: A Morphological Approach - Aswarini Sentana; Ratna Wulandari; Aulia Haris Firstiyanti (Asosiasi Dosen Muda Indonesia, 2025)
This research aims to analyze the morphological processes found in the lyrics of Taylor Swift's album, The Life of a Showgirl, specifically focusing on the use of derivational and inflectional affixes. The study utilizes the morphological theory proposed by William O’Grady to identify and categorize the affixes present in the selected songs. The research method employed in this study is the descriptive qualitative method, which allows for a detailed examination of the linguistic features within their natural context. The data were collected by identifying words containing affixes, with a strict protocol that ensured no repetition; thus, each data point represents a unique instance of a specific affix type, regardless of how many times the word is repeated in the song. The results of the analysis reveal a total of 239 affixes found in the album. Specifically, the data consists of 131 derivational affixes and 108 inflectional affixes. The findings indicate that derivational affixes are the dominant category used by the songwriter. This prevalence suggests that in The Life of a Showgirl, Taylor Swift prioritizes the process of word formation to alter meanings and grammatical categories, thereby enhancing the descriptive depth and rhyme scheme of the lyrics, while inflectional affixes are utilized to maintain grammatical cohesion and tense consistency.